FAKTOR-FAKTOR YANG MEMENGARUHI KEBUTUHAN PEGAWAI NEGERI SIPIL AKAN PEKERJAAN SAMPINGAN (STUDI KASUS KOTA BANDUNG DAN KABUPATEN SUMEDANG) - , MIRANTHY INDRIASTUTI IRIANTI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
It has become a common knowledge, where there are civil servants (PNS) in Indonesia, who has a secondary job (moonlighting), even though they are government employees with a guaranteed income every month. Using the sample data obtained from questionnaires on the scope of the civil servants in the City of Bandung and Regency of Sumedang, this study was made. The purpose of this study was to find out what factors that influence the need for civil servants to have secondary job, in the City of Bandung and Regency of Sumedang. This study use MWD test and regression analysis for cross-section data, and obtain the result that salaries, number of children that still need to be financed, location, and partner employment status, affect civil servants decision about secondary job, even though the variable of location has weak influence. Keywords: civil servants, PNS, secondary job, moonlighting, MWD test, cross-section, City of Bandung, Regency of Sumedang